UNIT 9.10 Installing a Local Copy of the Reactome Web Site and Knowledgebase. Issue 1 (19th June 2015) - McKay, Sheldon J.; Weiser, Joel
Abstract : The Reactome project builds, maintains, and publishes a knowledgebase of biological pathways. The information in the knowledgebase is gathered from the experts in the field, peer reviewed and edited by Reactome editorial staff, and then published to the Reactome Web site, http://www.reactome.org . The Reactome software is open source and builds on top of other open‐source or freely available software. Reactome data and code can be freely downloaded in its entirety and the Web site installed locally. This allows for more flexible interrogation of the data and also makes it possible to add one's own information to the knowledgebase. © 2015 by John Wiley & Sons, Inc.